2021
DOI: 10.7150/ijms.64658
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative neutrophil-to-lymphocyte, platelet-to-lymphocyte and monocyte-to-lymphocyte ratio as a prognostic factor in non-endometrioid endometrial cancer

Abstract: Objective: Evaluate the prognostic value of neutrophil-lymphocyte ratio (NMR), platelet-lymphocyte ratio (PLR), and monocyte-lymphocyte ratio (MLR) in patients with non-endometrioid endometrial cancer. Method: Laboratory and clinicopathological data from 118 patients with non-endometrioid endometrial cancer who underwent surgical resection between January 2010 and December 2019 were reviewed. NLR, PLR and MLR were analyzed for correlations with recurrence and survival. The receiver operating characteristic (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Conversely, the association between clinical T stage and prognosis for PSCC remains unclear. Moses et al reported 5-year CSS rates for pTis, pT1, pT2, and pT3/4 of 100%, 84%, 54%, and 54%, respectively [ 23 ]. Based on the National Cancer Database, local excision (39%) and partial penectomy (38%) were most commonly performed for patients with PSCC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the association between clinical T stage and prognosis for PSCC remains unclear. Moses et al reported 5-year CSS rates for pTis, pT1, pT2, and pT3/4 of 100%, 84%, 54%, and 54%, respectively [ 23 ]. Based on the National Cancer Database, local excision (39%) and partial penectomy (38%) were most commonly performed for patients with PSCC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that several factors for PSCC patients with ILNM, including the number of positive LN, the tumor grade of the involved nodes, the LNR, and the LN diameter, were histologically associated with PLNM [ 21 , 22 ]. According to CSS, PLNM (HR 2,07; p = 0.007) and bilateral LNM (HR 2.37; p < 0.001) were independent prognostic factors in the multivariate analysis, although PLND, bilateral LNM, ≥3 positive ILNM, and the LNM diameter were associated with CSS [ 23 ]. Zhao et al reported that the LNM size, particularly >2 cm, was an independent predictor with an objective response rate and oncological outcomes in patients with esophageal SCC who did not undergo surgical treatments [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The idea of to diagnose cancer through simple routine laboratory tests with a little amount of blood samples is worthy of investigation for many researchers. Some inflammatory markers including lymphocyte to monocyte ratio, neutrophil to lymphocyte ratio, albumin to globulin ratio were described previously , however, majority of these studies aimed to evaluate only the prognostic significant of the aforementioned markers in different cancer types (Stotz et al, 2014;Jia et al, 2015;Gu et al, 2016;Hsueh et al, 2017;Tan et al, 2018;Song et al, 2021;Tezuka et al, 2021;Atsumi et al, 2021;Castineiras et al, 2021;Mariani et al, 2022). There were a only a few studies had been published about association between systemic inflammatory markers and prediction of cancer diagnosis (Kocer et al, 2015;Li et al, 2017;Ataş et al, 2021) .…”
Section: Discussionmentioning
confidence: 99%
“…The monocyte-to-lymphocyte ratio (MLR) is a new inflammatory marker similar to NLR discovered in recent years. A Korean study on endometrial cancer displayed that high levels of MLR are prominently associated with cancer recurrence and cancer-related death (14). Interestingly, it has also been found to be associated with the severity and activity of some immune-related diseases such as multiple sclerosis, systemic lupus erythematosus, axial spondyloarthritis and ulcerative colitis (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%